Molecular Regulation and Rejuvenation of Muscle Stem (Satellite) Cell Aging - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2015)
BACKGROUND: Age-related muscle loss leads to lack of muscle strength, resulting in reduced posture and mobility and an increased risk of falls, all of which contribute to a decrease in quality of life. Skeletal muscle regeneration is a complex process, which is not yet completely understood.CONTENT: Skeletal muscle undergoes a progressive age-related loss in mass and function. Preservation of muscle mass depends in part on satellite cells, the resident stem cells of skeletal muscle. Reduced satellite cell function may contribute to the age-associated decrease in muscle mass. Recent studies have delineated that the aging process in organ stem cells is largely caused by age-specific changes in the differentiated niches, and that regenerative outcomes often depend on the age of the niche, rather than on stem cell age. It is likely that epigenetic states will be better define such key satellite cell features as prolonged quiescence and lineage fidelity. It is also likely that DNA and histone modifications will underlie many of the changes in aged satellite cells that account for age-related declines in functionality and rejuvenation through exposure to the systemic environment.SUMMARY: Skeletal muscle aging results in a gradual loss of skeletal muscle mass, skeletal muscle function and regenerative capacity, which can lead to sarcopenia and increased mortality. Although the mechanisms underlying sarcopenia remain unclear, the skeletal muscle stem cell, or satellite cell, is required for muscle regeneration. Decreased muscle stem cell function in aging has long been shown to depend on altered environmental cues, whereas the contribution of intrinsic mechanisms remained less clear. Signals in the aged niche were shown to cause permanent defects in the ability of satellite cells to return to quiescence, ultimately also impairing the maintenance of self-renewing satellite cells. Therefore, only anti-aging strategies taking both factors, the stem cell niche and the stem cells per se, into consideration may ultimately be successful.KEYWORDS: satellite cell, muscle, aging, niche, regenerations